Pengembangan LKPD Berbasis Guided Discovery Pada Materi Pewarisan Sifat Kelas IX SMP - Angeliana Desimaris Nita; Yohanes Bare; Sukarman Hadi Jaya Putra (Peneliti.net, 2022)
The advancement of science and technology has a significant influence on various of human life. One of them is education, an inseparable part of the human maturation process, which needs to take advantage of advances in science and technology to achieve its goals effectively and efficiently. The lack of student participation makes the material inheritance of traits in view easier. This research study aims to develop Guided Discovery-Based Learning on Inheritance Materials. The development model used is the 4D model. The results showed that the student worksheet grew declared very valid by material experts, media experts, and linguists. The student worksheet tested had an eligibility level with a category worthy of use in the trait inheritance material at SMP K Yapenthom 1 Maumere.